ANALYSIS OF OIL POWER TRANSFORMER RESOURCES THROUGH VIBRODIAGNOSTICS - Kodirov, Khusanhon Munavarkhan ugli; Yuldashev , Shukurullo Nematjon ugli (Educational Research in Universal Sciences, 2023)
The rapid methods of evaluating the technical condition of oil power transformers under operating conditions were studied. Determining the compressive strength of transformer coils by vibration control method reduces technical and economic costs.